Handwash Soap Production by Recycling Used Cooking Oil to Empower a Boarding School in Surakarta (Nusantara Science and Technology Proceedings, 2021)
Cooking oil is a primary good used for daily cooking purposes. In Indonesia, normally cooking oil is used up to four times frying. The used oil locally is referred to jelantah oil, blackish-brown colored, contains very high levels of cholesterol, and carcinogen, and it may cause harm for human health. Jelantah oil usually will be directly disposed of the environment, this may cause water and soil pollution. According to this, it is necessary to educate people to do reduction and recycle the used oil (jelantah), as will be done in Kanzus Sholawat Surakarta Foundation located in Sukoharjo, Central Java. The jelantah oil will be processed into handwash soap products with a feasible, easy, and cheap method and utilizing easily obtained material. To start, a 500 ml of used cooking oil is filtered and mixed with 160 grams of NaOH flakes soluted in 200 ml of water. Some drops of fragrance are added to make the soap perfumed. The purpose of this community service is to assist the Kanzus Sholawat Surakarta Foundation to take the economic value from the oil waste. The program will be carried out by training and guidance to process the jelantah oil into handwash soap, and continuous evaluation to make sure the Kanzus Sholawat Surakarta students and the nearby community get the optimal benefits. It is also expected that this activity can support the foundation's vision to become an environmentally minded institution.